Empreendedorismo institucional: o papel de empresas e suas associações na evolução da indústria de software e serviços no Brasil - Jacobus, Artur Eugênio (Universidade do Vale do Rio dos Sinos, 2014)
This study investigates the mutual influence between organizations and institutions, with special attention to episodes of institutional change. Taking the software and services industry in Brazil as an empirical object, we analyse the participation of companies and sectorial business associations in two processes of institutional change with effect on this industry. The main theoretical framework of this research is the literature on institutional entrepreneurship, a theoretical perspective associated with the organizational institutionalism, but we also seek support in the institutional economics and co-evolutionary approach. The two processes studied are the change of legislation on intellectual property of software, embodied in the Software Law of 1998, and the payroll tax reduction on software and services industry, which took effect in 2011. To understand how companies and business associations participated in these processes of institutional change, we carried out interviews with managers, leaders and former leaders of sectorial business associations, members of the Department of Information Technology Policy (Sepin) and a congressman. Moreover, we selected and analysed hundreds of documents with data about the processes of institutional change, from various sources, such as specialized news sites covering topics of the computer industry, records of sessions of Congress and studies prepared or commissioned by business associations. The analysis of interviews and documents revealed that business associations are used by companies to influence the Executive and Legislative Powers, as well as other actors in the organizational field, aiming to promote formal institutional changes that meet their interests. We reached the conclusion that the two institutional changes are eminently collective processes, considering the role of business associations and the need to build alliances with other actors. The research revealed that institutional entrepreneurship, in both studied cases, is starred by actors who have more resources and are at the centre of the organizational field, seeking to produce a setting of institutional homogeneity, through the implementation of a project of institutional harmonization with global reach or an initiative of institutional mimetism. Thus, this study contributes to the understanding of the role of collectives, such as business associations, in processes of institutional change. Finally, we present some suggestions for future research, such as comparing the evolution of regulation on intellectual property of software in different countries and monitoring the evolution of the form of taxation of software companies in Brazil after the validity period of the current legislation.
Keywords: Mudança institucional; Indústria de software e serviços; Associações empresariais; Propriedade intelectual de software; Desoneração da folha de pagamento; ACCNPQ::Ciências Sociais Aplicadas::Administração